2003
DOI: 10.1103/physrevb.68.205412
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of a sodium droplet onC60

Abstract: We investigate theoretically the progressive coating of C60 by several sodium atoms. Density functional calculations using a nonlocal functional are performed for NaC60 and Na2C60 in various configurations. These data are used to construct an empirical atomistic model in order to treat larger sizes in a statistical and dynamical context. Fluctuating charges are incorporated to account for charge transfer between sodium and carbon atoms. By performing systematic global optimization in the size range 1 ≤ n ≤ 30,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 79 publications
8
41
1
Order By: Relevance
“…From Na 3 C 60 − , the clustering of Na atoms starts, which was reported to start at the size of about 8 for both neutral and cationic sodium adsorbed fullerene clusters. 3,[16][17][18] The configuration for Na 3 C 60 speculated by Roques et al 18 is found to be around 0.2 eV higher in total energy for the anionic Na 3 C 60 − cluster, confirming the charge effects on the structures of small size clusters. [24][25][26][27][28] From the size of 5, the sodium aggregation configuration can be decomposed into the geometrical units of trimer and tetrahedron.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…From Na 3 C 60 − , the clustering of Na atoms starts, which was reported to start at the size of about 8 for both neutral and cationic sodium adsorbed fullerene clusters. 3,[16][17][18] The configuration for Na 3 C 60 speculated by Roques et al 18 is found to be around 0.2 eV higher in total energy for the anionic Na 3 C 60 − cluster, confirming the charge effects on the structures of small size clusters. [24][25][26][27][28] From the size of 5, the sodium aggregation configuration can be decomposed into the geometrical units of trimer and tetrahedron.…”
Section: Resultsmentioning
confidence: 74%
“…16 The segregated droplet formation of Na atoms above seven were also proposed by the empirical calculations 17 and the electric polarizability studies. 18 Recently, a density functional theory calculation 9 found a 4-atom island of Na atoms adhered to fullerene, in the line of the Na aggregation adsorption on C 60 . Besides the studies on Na aggregation, Palpant et al, based on the detailed photoelectron spectroscopy studies, proposed the packing of Na atoms of Na n C 60 − (n ≤ 12) in the form as trimer with each of the three Na atoms lying above the center of a pentagon, 6,7 being similar to the Li adsorption configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Detailed investigations on doped fullerene molecules with dopant atoms in substitutional (where the dopant substitutes one carbon atom from the cage), endohedral (where the dopant is inside the fullerene shell), and exohedral (where the dopant is outside fullerene shells) sites of the fullerene cage have been carried out experimentally as well as theoretically. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A large number of impurity atoms including the rare gas atoms, 5-9 lanthanides 10-12 alkali metals, 10 13-19 alkali earth metal, 20-21 transition metals, [21][22][23][24][25][26][27][28] main group elements [29][30] etc., have been successfully used in the doping of fullerenes. The direct production of fullerenes in the presence of foreign species may lead to endohedral [8][9][10] or substitutional fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Other than HF and post-HF methods, the density functional theory formalism has also been employed by several workers to obtain the information regarding the location of impurity and the interaction between impurity and fullerene molecule. [44][45][46][47][48][49][50][51] Discrete-variational local density functional calculations were performed on the endohedral NC 60 , OC 60 and FC 60 clusters by Lu et al They have found that the non-metallic N, O and F atoms are not covalently bonded to the cage and they nearly keep atomic electronic configuration unaltered. 46 Batista and co-researchers investigated the possible formation of Au-covered carbon fullerenes by means of first-principles calculations at the DFT/GGA level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation